DECISION MAKING IN EPILEPTIC AVMS - Adrian Balasa (Romanian Neurosurgery)
While there is no doubt about the need for surgical treatment of a ruptured arteriovenous malformation (AVM), the decision to surgically treat a patient presenting solely with seizures is more controversial.